PENGARUH EKSTRAK KULIT BAWANG MERAH DALAM MENGENDALIKAN HAMA ULAT GRAYAK (Spodoptera litura F.) SECARA IN VITRO - Gusriani, Yunda; BENAULI, ARKHIADI; SULASTRI, YUSTINA SRI (Agroprimatech, 2023)
This research was conducted to determine the dose of shallot skin extract that is effective for controlling Spodoptera litura F. This research was carried out for 2 months at the Biology Laboratory, Faculty of Agriculture, Santo Thomas Catholic University, Medan. The research design used was a Non-Factoral Completely Randomized Design (CRD) consisting of five treatments and each treatment was repeated four times to form 20 experimental units of Red Onion Skin Soaking (K), namely: K0 = 0% (Control), K1 = 20 gr/liter of water, K2 = 40 gr/liter of water, K3 = 60 gr/liter of water, and K4 = 80 gr/liter of water. The parameters observed were pest mortality, 50% death time and larval behavior after application. From the research results, it can be seen that administering shallot skin extract at the highest dose, namely 80 g/L, can be quadratically used as a botanical insecticide to control S. litura pests with a death time of 27 hours